Recovery of left ventricular systolic function after left anterior descending coronary artery stenting - (:unkn) unknown (My University, 2005)
Our objective was to determine the factors affecting recovery of left ventricular (LV) contractility and myocardial perfusion after percutaneous coronary intervention (PCI). We selected 60 consecutive patients who underwent successful left anterior descending coronary artery (LAD) stenting. The mean stent diameter and length were 3.37 ± 0.47 mm and 17.4 ± 6 mm, respectively. Supporting a functional impact of successful PCI, myocardial perfusion and LV ejection fraction (LVEF) improved at 6 ± 3 months after the procedure (48.8 ± 11.6% vs 52.5 ± 11.5%, P = 0.05). Patient related factors such as diabetes mellitus, presentation with acute coronary syndrome, and age did not seem to affect LVEF change after the procedure. On univariate analysis, the change in LVEF after PCI was only related to the stent diameter. The increase in LVEF was higher in patients who received a stent >3 mm in diameter (P = 0.041). There was a weak but statistically positive correlation between the stent diameter and the LVEF change after the procedure (R = 0.267, P = 0.049). Other procedure related factors such as multivessel PCI or stent length did not affect the percent ejection fraction change after stenting.